Dynamic processes in surface layers of parts as a source of their multicycle failure under friction and wear - Malinovskyi, Y.O.; Mikosianchyk, O.O.; Uchytel, O.D.; Skvortsov, O.O.; Vlasenkov, D.P.; Sytnyk, S.O.; Oliinyk, S.Y. (Problems of Tribology, 2025)
During the operation of various machines and mechanisms, oscillatory movements may occur, excited by a non-stationary friction characteristic. These oscillations appear either at the contact area of two parts or in the zone located ahead of the moving part. In the contact area, a non-stationary friction force develops, leading to self-excited oscillations of the contact surface and to the occurrence of parametric oscillations in the area ahead of the active punch. At certain ratios of slip velocities and part movement speeds, self-excited and parametric motions may appear or disappear, as well as intensify or weaken. These oscillations are one of the causes of uncontrolled surface roughness (deformational), cracking, and spalling of interacting parts, as well as significant dynamic components during the loading of actuating, drive, and power mechanisms. Frictional and parametric oscillations in the surface layers of parts with deformation wave formation create residual plastic sinusoidal metal layers, which are sheared off during the interaction of parts. Due to the dynamic nature of interaction during friction, the forces acting in the contact plane (longitudinal) exceed the critical Euler force, which is a parametric load, and in some cases lead to dangerous parametric resonance. The work defines the frequency range near the parametric resonance, which is the area of dynamic instability ahead of the moving punch. The formulated and partially solved problem considers frictional and parametric oscillations during the interaction of parts, which lead to the formation of deformation waves.